Centurion Syndrome- Rarity Revisited - Bijnya Birajita Panda; Jyotsna Sharma (Delhi Journal of Ophthalmology)
Centurion syndrome is a rare cause of unexplained epiphora which often goes unrecognized due to a lack of awareness among ophthalmologists. This entity should be considered in the differential diagnosis of causes of epiphora which can be managed surgically. This article is a short review of the available literature on etiopathogenesis, clinical features, diagnosis, and current management of Centurion syndrome.